The future of the ODA concept: the political dimensions of a seemingly technical discussion - Stephan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
There is a possibility that the development ministers of the Organisation for Economic Co-operation and Devel¬opment (OECD) will agree on a new definition of official development assistance (ODA) at the end of 2014. Ongoing discussions on this matter may appear purely technical at first glance. While there is a range of specific technical aspects to the concept and development of ODA, it is becoming clear that the debate about a suitable new definition covers the entire spectrum of development policy topics involving structural change. Consequently, the current ODA debate reflects the various perspectives within the policy area as a whole. Do we simply need to make a few internal system adjustments to the ODA concept or might we in fact be seeing the beginning of the end of development cooperation as we know it, particularly as we have known it since the early 1960s? Is the provision of outside support to poor countries becoming obsolete as a model of international policy? There are two key reasons why the OECD countries agreed on an internationally applicable concept of ODA to begin with. Firstly, it allows standards and, by extension, qualitative requirements to be defined that distinguish ODA from other approaches to cooperation, such as instruments for promoting foreign trade and military cooperation with other states. Secondly, it makes it possible to keep quantitative records of contributions to development and of comparisons between countries that play a part in collective global action. Experience over the last few decades has shown that providing comparative inter¬national data can indeed put a degree of pressure on governments and parliaments to pursue or increase development cooperation activities. The United States, for instance, has never made a specific commitment to provide 0.7 percent of its economic output as ODA, a target generally accepted by donors. The European Union countries have attempted to flesh out this target in a step-by-step plan, yet have failed to achieve it on numerous occasions. For a long time, the Scandinavian countries and (until 2012) the Netherlands were considered to be role models in achieving the 0.7 percent target, and now the United Kingdom has also taken on a leading role in this respect, having recently enshrined the target in its legislation. Discussion about this target shows that statistical measurement has most definitely provided an international incentive for countries to increase their inputs.
Keywords: 330; Aufstrebende Mächte; Deutsche + Europäische + multilaterale Entwicklungspolitik